Differences in performance indicators of elite tennis players in the period 1991-2010 - Filipcic, A.; Zecic, M.; Reid, M.; Crespo, M.; Panjan, A.; Nejc, S. (Journal of Physical Education and Sport, 2015)
The aim of this study was to compare differences in 15 tennis match variables between two groups of top 300 male ATP (Association Tennis Professionals) players. The groups consisted of the top 300 ATP players who had positive win-loss number of matches (G_1) and negative win-loss number of matches (G_2) in professional tennis tournaments at three different points in time, approximately 10 years apart (1991, 2000 and 2010). A t-test for independent samples and multivariate ANOVA (MANOVA - Wilks` lambda) assessed the differences between the two groups of players. The comparisons revealed that players in Group 1 achieved a significantly better statistical performance in selected aspects of the serve, the return and in general matchplay, independent of the year. The largest number of differences in the analysed match statistics was observed in 2010, where 12 match statistics varied significantly between the two groups. Some evidence also suggests that the efficiency of the serve and return of serve have improved over the past two decades, therein highlighting their important role in modern professional tennis. The present findings suggest that the observed performance indicators are sufficiently sensitive to discriminate between top 300 ATP players with variable number of winloss matches.